Dry Matter Yield of Maize (Zea mays L.) as an Indicator of Mineral Fertilizer Efficiency - Piotr Szulc; Katarzyna Ambroży-Deręgowska; Hubert Waligóra; Iwona Mejza; Stanisław Grześ; Waldemar Zielewicz; Barbara Wróbel (Plants, 2021)
This study presents the results of 3-year field trials, whose purpose was to assess the dynamics of dry matter accumulation by maize depending on the placement depth of a two-component (NP) mineral fertilizer in the soil layer, type of nitrogen fertilizer and date of its application. Weather conditions, mainly thermal in the early growing season, had a significant effect on maize responses to placement depth of phosphorus starting dose in the soil profile. In the initial stage of maize development, the temperature determined plant growth to a significantly higher extent than the sum of rainfall. The dry matter yield of ears and whole plants showed a clear reaction to starter phosphorus fertilization, but the effect of the depth of fertilizer placement varied over the years, indicating a depth of 5 cm and 10 cm as advisable and recommended for agricultural practice. The PFPFN (partial factor productivity of fertilizer nitrogen) and PFPFP (partial factor productivity of fertilizer phosphorus) indices confirmed the significant effect of fertilizer (NP) placement in the soil profile, indicating row fertilizer application (regardless of the depth) as recommended to improve the efficiency of maize fertilization. The SPAD (soil plant analysis development) leaf greenness index turned out to be a sensitive indicator of maize response to fertilizer (NP) placement depth in the soil profile.